x-9-5=7-x-76

Simple and best practice solution for x-9-5=7-x-76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-9-5=7-x-76 equation:


Simplifying
x + -9 + -5 = 7 + -1x + -76

Reorder the terms:
-9 + -5 + x = 7 + -1x + -76

Combine like terms: -9 + -5 = -14
-14 + x = 7 + -1x + -76

Reorder the terms:
-14 + x = 7 + -76 + -1x

Combine like terms: 7 + -76 = -69
-14 + x = -69 + -1x

Solving
-14 + x = -69 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-14 + x + x = -69 + -1x + x

Combine like terms: x + x = 2x
-14 + 2x = -69 + -1x + x

Combine like terms: -1x + x = 0
-14 + 2x = -69 + 0
-14 + 2x = -69

Add '14' to each side of the equation.
-14 + 14 + 2x = -69 + 14

Combine like terms: -14 + 14 = 0
0 + 2x = -69 + 14
2x = -69 + 14

Combine like terms: -69 + 14 = -55
2x = -55

Divide each side by '2'.
x = -27.5

Simplifying
x = -27.5

See similar equations:

| 3-11=-8 | | -34=-2y+3y | | 4+2s=3s-7 | | x^2+4x+18=40 | | 3x^2+23=-13 | | 7n-16n+4=0 | | -a+7(1+3a)-20=0 | | 2x+40=.182x | | 18x+3=10x-45 | | -(m-6)=3m+4 | | x^2+4x-18=40 | | 6x+8-2=-24 | | 12/m-3 | | -5x+16+-8(x+1)=6x | | 2x^2-3y^2=12 | | 4m/m-3 | | -3+7=-5 | | -6x-x+10=15-7x | | 1-n-5+16=-n-2n | | (9v+36)(v^2-6v+5)=0 | | -(x+7)-6=-20+6x | | N^2+16=-8n | | 3[4x-5(y-2)]= | | -3x-1=x-17 | | -5=9+4 | | X+4(x+2)=12 | | -2(9+4s)=34 | | 5a^2= | | 3a+12=6a+7 | | 4x^3-6x-6=0 | | -7(1-5h)=21 | | 3x+2y+2x+5z+7y+2z= |

Equations solver categories